2020
DOI: 10.1016/j.jtrangeo.2020.102894
|View full text |Cite
|
Sign up to set email alerts
|

Are stay-at-home orders more difficult to follow for low-income groups?

Abstract: In response to the COVID-19 pandemic, a growing number of states, counties and cities in the United States issued mandatory stay-at-home orders as part of their efforts to slow down the spread of the virus. We argue that the consequences of this one-size-fits-all order will be differentially distributed among economic groups. In this paper, we examine social distance behavior changes for lower income populations. We conduct a comparative analysis of responses between lower-income and upper-income groups and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 37 publications
7
66
0
1
Order By: Relevance
“…With respect to the literature, these results are consistent with studies such as by Alexander and Karger (2020) who have shown that residents of high‐income counties began reducing their movement well before stay‐at‐home orders went into effect or studies such as by Lou and Shen (2020) who have shown that social‐distance‐policy effects on the lower‐income group is smaller than that of the upper‐income group or studies such as by Ruiz‐Euler, Privitera, Giuffrida, Lake, and Zara (2020) who have shown that the decline in human mobility during COVID‐19 happened at different speeds for high versus low income groups within most US cities.…”
Section: Estimation Resultssupporting
confidence: 90%
“…With respect to the literature, these results are consistent with studies such as by Alexander and Karger (2020) who have shown that residents of high‐income counties began reducing their movement well before stay‐at‐home orders went into effect or studies such as by Lou and Shen (2020) who have shown that social‐distance‐policy effects on the lower‐income group is smaller than that of the upper‐income group or studies such as by Ruiz‐Euler, Privitera, Giuffrida, Lake, and Zara (2020) who have shown that the decline in human mobility during COVID‐19 happened at different speeds for high versus low income groups within most US cities.…”
Section: Estimation Resultssupporting
confidence: 90%
“…Additionally, lower-income populations participate less in social distancing, likely in part because low-wage workers may have less access to job protections or paid leave. Our results provide further nuance to the analysis by Lou et al [ 9 ], who found that lower-wage workers were unable to reduce their work trips, in large part because businesses classified as essential tended to pay lower wages. Our results may help explain why lower-income counties have suffered a disproportionately high death burden from COVID-19 [ 17 ]; however, these results also need to be taken in light of the more general role that low income plays in negative health outcomes [ 21 ].…”
Section: Discussionsupporting
confidence: 75%
“…However, social distancing may be adopted differently across communities, especially in the United States, where workers in sectors such as transportation and food retail receive lower wages and represent a larger fraction of workers deemed essential than those in other sectors of the workforce [ 8 , 9 ]. Assessing this differential impact requires the use of fine-scale mobility data, a stream of information that has proven useful in the early assessment of social distancing measures in the United States [ 10 ], Italy [ 11 ], and France [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the “Stay-At-Home (SAH)” message promoted across the globe and the “Work-From-Home (WFH)” reality subsequently achieved whenever possible [ 16 ], it is still unclear to what extent individuals have modified their attitude in response to the bans on free movement [ 17 ]. As mobility is closely connected to regular habits and reproducible patterns [ 18 ], the restrictive measures can represent a “game changer” for all of society entailing permanent behavioral effects comparable to life events and structural shifts among travel modes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%